Doppler broadening spectroscopy of carbon black and carbon black-filled rubbers - Semaan, Mars E. (2001)
We have used positron annihilation Doppler broadening spectroscopy to investigate the effects of filling various rubber polymers with different amounts and types of carbon blacks. The results show direct correlation between various physical properties of the carbon black and the Doppler broadening of the positron annihilation gamma ray. The Doppler broadening is characterized by the S parameter, which is a measure of the fraction of the positrons that annihilate with low-momentum valence electrons or from positronium in the sample. The S parameter decreases as carbon black is added to the rubber. The decrease in the S parameter depends on the type and morphology of the carbon black. This is due to (1) reduction in positronium formation as carbon black is added to the rubber, and (2) positron trapping at the carbon black–rubber interface, which depends on the carbon black morphology. The S parameter decreases with the carbon black surface area. The S parameter does not depend on the sample mixing time.